Synthesis, electrochemical behavior and X-ray crystal and molecular structures of [Fe(diene)(CO)(2)PPh3] (diene = chalcone, sorbic acid) - Zutin, K.; Nogueira, V. M.; Mauro, A. E.; Melnikov, P.; Iluykhin, A. (Elsevier B.V., 2001)
The compounds [Fe(ch)(CO)(2)PP3] (1) (ch = chalcone) and [Fe(sba)(CO)(2)PPh3] (2) (sba = sorbic acid) were prepared by irradiating the tetracarbonyltriphenylphosphineiron(0) complex in benzene in the presence of ch or sba. The compounds were characterized by infrared and P-31 NMR spectroscopies. Their electrochemical behavior was investigated by cyclic voltammetry and the results suggest that their oxidations occur by more than one electrochemical step, producing free ch and sba, free PPh3 and solvated Fe(III). It was observed that sba ligand contributes more effectively to the stabilization of metal center in these complexes, the X-ray crystal and molecular structures of 1 and 2 were determined; it was shown that the Fe atom adopts a distorted octahedral coordinated geometry in which three of the sites are occupied by the ch or sba ligand. The [Fe(ch)(CO)(2)PPh3] complex is a monomer and the unit cell of complex 2 contains exist two identical and crystallographically independent molecules of [Fe(sba)(CO)(2)PPh3] which are linked by short hydrogen bonds O-H . . .O (C) 2001 Published by Elsevier B.V. Ltd.
Keywords: dicarbonyliron complexes; chalcone; sorbic acid; X-ray structures; cyclic voltammetry